Nonhomologous end joining and homologous recombination involved in luteolin-induced DNA damage in DT40 cells. (June 2020) - Xiang, Cuifang; Wu, Xiaohua; Zhao, Zilu; Feng, Xiaoyu; Bai, Xin; Liu, Xin; Zhao, Jingxia; Takeda, Shunichi; Qing, Yong
Abstract: Luteolin (3′, 4′, 5, 7-tetrahydroxyflavone), a naturally occurring flavonoid, has been shown to have anticancer activity in many types of cancer cell lines. The anticancer capacity of luteolin may be related to its ability to induce DNA double-strand breaks (DSBs). Here, we used DT40 cells to determine whether nonhomologous end joining (NHEJ) and homologous recombination (HR) are involved in the repair mechanism of luteolin-induced DNA damage. Cells defective in Ku70 (an enzyme associated with NHEJ) or Rad54 (an enzyme essential for HR) were hypersensitive and presented more apoptosis in response to luteolin. Moreover, the sensitivity and apoptosis of Ku70 −/− and Rad54 −/− cells were associated with increased DNA damage when the numbers of γ-H2AX foci and chromosomal aberrations (CAs) were compared with those from WT cells. Additionally, after treatment with luteolin, Ku70 − / − cells presented more Top2 covalent cleavage complexes (Top2cc). These results indicated that luteolin induced DSBs in DT40 cells and demonstrated that both NHEJ and HR participated in the repair of luteolin-induced DSBs, which might be related to the inhibition of topoisomerases. These results imply that simultaneous inhibition of NHEJ and HR with luteolin treatment would provide a powerful protocol in cancer chemotherapy. Graphical abstract: Unlabelled Image Highlights: Luteolin inhibited cell survival and induced DNA double strand breaks (DSBs)in DT40 cells. Nonhomologous end joining (NHEJ) is critical in response to luteolin induced DNA damages. Homologous recombination (HR) had a role in tolerance of luteolin induced DSBs.